Kepentingan Ekonomi Dibalik Respon Pemerintah Cina Terhadap United State Trade Representative (USTR) Notorious Markets List Tahun 2016–2018 - Ananda Fitria Trisnawati; Ika Riswanti Putranti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The United States and China are the two largest economic powers in the world today. Therelationship between the two countries always change from time to time in accordance withthe circumstances. Despite the cooperation in various fields, concerns and disputes remaininevitable. One of the disputes between the two countries is the protection of intellectualproperty rights. The dispute is more or less due to differences in the application of intellectualproperty rights protection regimes in each country. The United States had implemented theintellectual property protection regime long ago before China implemented the intellectualproperty protection regime. The United States institution in charge of handling this matter isthe United State Trade Representative (USTR). USTR gave its recommendations through theNotorious Markets List which then often targets the largest e-commerce from China, Taobaowhich is a subsidiary of the Alibaba Group. This study then aims to analyze the reasons behindthe response given by the Chinese government to the USTR's Notorious Markets List, especiallyin 2016-2018. These factors will be analyzed using the concept of national interest. Thisresearch argues that the response given by the Chinese government to USTR's 2016 NotoriousMarkets List is not only about the intellectual property agenda but there is an economic interestbehind it.